Evidence-based geriatic nursing protocols for best practice - Boltz, Marie ;Capezuti, Elizabeth;Fulmer, Terry;Zwicker, Deanne (New York : Spinger Publishing Company, 2016)
The new fifth edition of one of the premier references for geriatric nurses in hospital, long-term, and community settings delivers current guidelines, real-life case studies, and evidence-based protocols developed by master educators and practitioners. With a focus on improving quality of care, cost-effectiveness, and outcome, the fifth edition is updated to provide the most current information about care of common clinical conditions and issues in older adults. Several new expert contributors present current guidelines about hip fractures, frailty, perioperative and postoperative care, palliative care, and senior-friendly emergency departments. Additionally, chapters have been reorganized to enhance logical flow of content and easy information retrieval. Protocols are organized in a consistent format and include an overview, evidence-based assessment and intervention strategies, and an illustrative case study with discussion. Additionally, protocols are embedded within chapter text, providing the context and detailed evidence for each. Chapter objectives, annotated references, and evidence rating for each protocol are provided along with resources for additional study. -- Provided by publisher. The new fifth edition of one of the premier references for geriatric nurses in hospital, long-term, and community settings, delivers current guidelines, real-life case studies, and evidence-based protocols developed by master educators and practitioners. Several new expert contributors present current guidelines about hip fractures, frailty, perioperative and postoperative care, palliative care, and senior-friendly emergency departments
Developing and evaluating clinical practice guidelines : a systematic approach / Rona F. Levin and Susan Kaplan Jacobs -- Measuring performance, improving quality / Lenard L. Parisi -- Age-related changes in health / Constance M. Smith and Valerie T. Cotter -- Health care decision making / Linda Farber Post and Marie Boltz -- Sensory changes / Pamela Z. Cacchione -- Assessing cognitive function / Pieter Heeren, Johan Flamaing, Jos Tournoy, Marquis D. Foreman, and Koen Milisen -- Assessment of physical function / Denise M. Kresevic -- Oral health care / Linda J. O'Connor -- Managing oral hydration / Janet C. Mentes -- Nutrition / Rose Ann DiMaria-Ghalili -- Family caregiving / Deborah C. Messecar -- Issues regarding sexuality / Elizabeth E. Steinke -- Mistreatment detection / Billy A. Caceres and Terry Fulmer -- Preventing functional decline in the acute care setting / Marie Boltz, Barbara Resnick, and Elizabeth Galik -- Late-life depression / Glenise L. McKenzie and Theresa A. Harvath -- Dementia : a neurocognitive disorder / Kathleen Fletcher -- Delirium : prevention, early recognition, and treatment / Dorothy F. Tullmann, Cheri Blevins, and Kathleen Fletcher -- Pain management / Ann L. Horgas, Mindy S. Grall, and Saunjoo L. Yoon -- Preventing falls in acute care / Deanna Gray-Miceli and Patricia A. Quigley -- Reducing adverse drug events / DeAnne Zwicker and Terry Fulmer -- Urinary incontinence / Annemarie Dowling-Castronovo and Christine Bradway -- Prevention of catheter-associated urinary tract infection / Heidi L. Wald, Regina M. Fink, Mary Beth Flynn Makic, and Kathleen S. Oman -- Physical restraints and side rails in acute and critical care settings / Cheryl M. Bradas, Satinderpal K. Sandhu, and Lorraine C. Mion -- Preventing pressure ulcers and skin tears / Elizabeth Ann Ayello and R. Gary Sibbald -- Mealtime difficulties in dementia / Melissa Batchelor-Murphy and Sarah Crowgey -- Excessive sleepiness / Grace E. Dean, Michelle L. Klimpt, Jonna Lee Morris, and Eileen R. Chasens -- The frail hospitalized older adult / Stewart M. Bond, Rebecca Bolton, and Marie Boltz -- Substance misuse and alcohol use disorders / Madeline Naegle and Donna McCabe -- Comprehensive assessment and management of the critically ill / Michele C. Balas, Colleen M. Casey, Lauren Crozier, and Mary Beth Happ -- Fluid overload : identifying and managing heart failure patients at risk of hospital readmission / Judith E. Schipper -- Cancer assessment and intervention strategies / Janine Overcash -- Perioperative care of the older adult / Fidelindo Lim and Larry Z. Slater -- General surgical care of the older adult / Larry Z. Slater and Fidelindo Lim -- Care of the older adult with fragility hip fracture / Anita J. Meehan, Ami Hommel, Karen Hertz, Valerie MacDonald, and Ann Butler Maher -- Acute care models / Elizabeth Capezuti, Ana Julia Parks, Marie Boltz, Michael L. Malone, and Robert M. Palmer -- Transitional care / Fidelindo Lim, Janice B. Foust, and Janet H. Van Cleave -- Palliative care models / Constance Dahlin -- Care of the older adult in the emergency department / Marie Boltz and Amala Sooklal -- Advance care planning / Linda Farber Post and Marie Boltz
Includes bibliographical references and index.
Keywords: NURSING ASSESSMENT